Active Suspension using Optimal Controller - Ab Ghani, Mohd Ruddin; Mat Youb, Norsarizan; Sakidin, Hamzah; Syed Najib , Syed Salim (2010)
The purpose of the project is to design controller for active suspension using optimal control method. In order to reach the main objective, the behavior of passive suspension is studied correspond to the different types of road surface. The controller will improve the ride quality and handling performance within a given suspension stroke limitation. The problems of passive control are excessive vertical wheel travel, non-optimum altitude of tire relative to road, also the force distribution of the suspension, resulting poor handling, body roll or body pitch when braking or accelerating and ride discomfort. This problem will be overcome by using active control suspension which the method chosen is optimal controller. The performance of this controller is determined by performing computer simulations using the MATLAB and SIMULINK. The results show that the active suspension system has reduced the peak overshoot of sprung mass displacement, sprung mass acceleration, suspension travel and tire deflection compared to passive suspension system.